Local PMT Product Innovation and Optimization of Teenage girl's Potential in Preventing Stunting in Lajuk Village, Gondang Wetan Subdistrict, Pasuruan Regency - Winarningsih, Wiwik (Journal of Dedicators Community, 2024)
Based on health data from Lajuk Village in 2022, out of 200 babies and toddlers in Lajuk village, there are 39 cases of stunting that need to be handled, if the percentage is 20% of the total number of toddlers there. One of the causes of the high stunting rate in Lajuk Village is the community's lack of independence in providing balanced nutritional intake. Based on these findings, the author proposes an innovation activity program to create local PMT and optimize the potential of teenage girls who can become cadres in preventing stunting in Lajuk village.Methods: The series of activities in this research include providing counseling, training on making Supplementary Food (PMT) from local ingredients, implementing the PMT program for children and toddlers, as well as the formation of the Stunting-Free Teenage Girl's Cadre Group (BESTING).Results and Discussion: It is known that the post-test results showed that the majority of respondents (84%) had a good assessment from the previous pretest results; only 42% showed an increase in knowledge. After the series of interventions were implemented, there was a reduction in the stunting rate in Lajuk Village from previously 20 toddlers in May 2023 to 12 toddlers in August 2023.Conclusion: Mobilizing and using the potential of teenage girls in Lajuk Village is one way to reduce the stunting rate in Lajuk Village. With the formation of BESTING Cadres, it is hoped that it will be able to reduce the stunting rate in Lajuk Village.